Assessing the Effect of Traditional Games on Manipulative Movements in Elementary School Students Based on Gender - Nugroho Puji Santoso; Subagyo; Nurhadi Santoso; Trisnar Adi Prabowo; Wahyu Dwi Yulianto (OVS LLC, 2024)
Background. Manipulative movements are essential for children's development, which can be found in traditional games, representing manifestation of local wisdom that has been passed down from generation to generation. Objectives. This study aimed to examine the effect of traditional games on the manipulative movements of elementary school students based on gender. Materials and methods. This experimental study comprised two pretest-posttest groups without control variables. Data collection on pretest and posttest was carried out using three types of tests, namely throwing, catching, and kicking. A total of 60 students aged between 9 and 12 years were selected to participate in this study. The sample consisted of 30 male students (height 140.21±6.2 cm, and weight 35.77±5.6 kg), and 30 female students (height 138.4±6.8 cm and weight 34±4.1 kg). Results. The t-test analysis showed that the test results for male students were as follows: throwing 0.011<0.05, catching 0.007<0.05, and kicking 0.003<0.05. Then, the test results for the female students were: throwing 0.013<0.05, catching 0.017<0.05, and kicking 0.012<0.05. The results of the independent t-test indicated that the throwing, catching, and kicking tests revealed a statistical significance (p < 0.05) in both male and female students. Conclusions. The implementation of traditional games has been found to enhance the manipulative movements of elementary school students, as evidenced by positive changes observed in the pretest and posttest results. The improvement was achieved, among others, through the adaptation of traditional games following the characteristics of students' development. Therefore, the conceptualization of physical learning within the framework of traditional games proved to be applicable and practical.